C-CHIL: A NEW LEARNING MODEL FOR ADVANCED MATHEMATICS COURSE IN THE SOCIETY 5.0 ERA - M.J. Dewiyani Sunarto; Bambang Hariadi (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
University graduates in the Society 5.0 era need more skills than ever before; thus, a new learning model is needed. To respond this situation, we created a learning model that equips students to think critically, creatively, and independently through Advanced Mathematics courses using hybrid learning. This study aims to produce a model that can meet the needs of Moodle-based hybrid learning. Through research and development (R&D), we developed a learning model through the “Brillian” application. The Critical Creative Hybrid Independent Learning (C-CHIL) model test was conducted regarding (1) quality which includes the content and constructs of the model, and (2) feasibility. The test results of the C-CHIL model show that (1) Content validity test resulted an average of 3.73 which means the model is very valid. (2) The average feasibility test is 3.63, which means it is also very valid. Thus, it can be concluded that the C-CHIL model meets the valid requirements (content and construct) and is suitable for students based on expert opinion. The results of this study imply that the C-CHIL model can be used to improve critical, creative, and independent thinking skills, especially in Advanced Mathematics courses in Higher Education